A Goofy movie [videorecording (DVD)] - Lima, Kevin (Walt Disney gold classic collection., 2000)
This rockin' and rollin' modern-day story finds Goofy bonding with his teenage son, Max, on a cross-country road trip. But en route to the ol' fishing hole, they find themselves up to their floppy ears in misadventure! Will Max learn there's nothing wrong with taking after dear old dad-- even if he is a little goofy?